Politics has no religion - Ra'ees, Wahabuddin (2017)
Centuries-long Western view that religion has no social role and does not have anything to offer to humanity and human political organization is still prevalent in academic discussion. Separation between religion and politics has always been seriously debated and discussed. While Islam does not subscribe to secularism and separation of religion and politics, yet many in the Muslim World argue that religion should not be politicized. Many see this trend as deviation from Islam’s original approach to relationship between religion and politics, yet some argue that some Islamists groups and parties in the Muslim World such as Turkey, Tunisia and Egypt under President Mohammad Morsi adopted secularism as a strategy rather than state philosophy to convince their secular citizens that they all can live in harmony in under one roof or political system.